2022
DOI: 10.1002/advs.202105336
|View full text |Cite
|
Sign up to set email alerts
|

Lonely in the Dark: Trauma Memory and Sex‐Specific Dysregulation of Amygdala Reactivity to Fear Signals

Abstract: Loneliness exacerbates psychological distress and increases the risk of psychopathology after trauma exposure. However, it is still unclear whether a lack of social connectedness affects trauma-related intrusions and the neural processing of fear signals. Moreover, it is uncertain, whether loneliness plays a different role in women and men. A prestratification strategy is used and n = 47 (n = 20 women) healthy lonely individuals and n = 35 controls (n = 18 women) are recruited. Participants are exposed to an e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 83 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…In the field study, however, our exploratory analysis showed that gender was not related to any of the outcomes, and it did not interact with type of day. Given recent evidence suggesting gender-related neurophysiological effects of chronic loneliness (Morr et al, 2022; Spreng et al, 2020), future studies will need to test the effects of acute social isolation on energy and fatigue in men as well as women to confirm the generalizability of these findings. It is worth highlighting the correlational nature of the field study so we could not establish the causality of the found effects.…”
Section: Discussionmentioning
confidence: 99%
“…In the field study, however, our exploratory analysis showed that gender was not related to any of the outcomes, and it did not interact with type of day. Given recent evidence suggesting gender-related neurophysiological effects of chronic loneliness (Morr et al, 2022; Spreng et al, 2020), future studies will need to test the effects of acute social isolation on energy and fatigue in men as well as women to confirm the generalizability of these findings. It is worth highlighting the correlational nature of the field study so we could not establish the causality of the found effects.…”
Section: Discussionmentioning
confidence: 99%
“…We used ancestry-specific LD references for ancestry-specific GWASs, cross-ancestry LD reference for crossancestry GWASs, as well as ancestry-and sex-specific LD references for sex-stratified GWASs. These LD references were constructed based on imputed genotype data from 35,474 (16,899 males and 18,575 females) UKB and 6,923 (2,397 males and 4,526 females) CHIMGEN participants. Since the sample sizes of EUR-GWASs were at least four times greater than those of EAS-GWASs, for the sake of simplicity, we used the EUR-LD reference to pool GWAS results and to identify new associations and loci.…”
Section: Imaging Phenotypes Association Statistics and Ld Referencesmentioning
confidence: 99%
“…Furthermore, patients with substance abuse [64][65][66], borderline personality disorder [67,68], and schizoid personality disorder [69] report more loneliness and social disconnection than healthy controls. In addition, loneliness is a potential risk factor for post-traumatic stress disorder [70,71] and enhances intrusive thoughts after trauma exposure [72,73]. Overall, loneliness and social isolation are critical risk factors for several somatic and mental disorders and thus should be considered in therapeutic protocols.…”
Section: Detrimental Health Consequences Of Lonelinessmentioning
confidence: 99%
“…Of note, a recent study found that loneliness may influence trauma memory in a sex-dependent manner. Specifically, lonely men, but not lonely women, exhibited more intrusive thoughts after experimental trauma and this phenotype was related to amygdala hyperreactivity during both fear conditioning and habituation processes, suggesting that the limbic system is a potential target for interventions that increase social connectedness [73]. Furthermore, the above-mentioned alterations in hippocampus-DMN covariation may reflect the neurobiological basis for an increased negative memory retrieval [92].…”
Section: Memory and Working Memorymentioning
confidence: 99%
See 1 more Smart Citation